Islam and the Australian news media - Rane, Halim, 1976-; Ewart, Jacqui; Abdalla, Mohamad (Carlton, Vic. : Melbourne University Press, an imprint of Melbourne University Pub., 2010)
"Few issues have captured media headlines over the past two decades like Islam and Muslims, and much of what the Australian public knows about Islam and its followers is gleaned from the mass media. Islam and the Australian News Media tackles head-on the Australian news media's treatment of Islam and Muslims. This incisive collection brings together the research and insights of academics, editors and journalists on the representation of Islam and its impact on social relations, the newsworthiness of Muslim issues and the complexities of covering Islam. Importantly, Islam and the Australian News Media also explores how Muslim communities in Australia are responding to their image in the Australian news media. This book is a must-read for all those interested in the relationship between media and society."--Publisher description.
Includes bibliographic references and index.
Keywords: Islam -- Press coverage -- Australia; Islam in mass media; Islam and civil society -- Australia; Mass media -- Objectivity -- Australia; Muslims -- Australia -- Attitudes; Australian